Visualization of Food Bank/Agency Distribution. (November 2019) - Delpish, Ritson; Jiang, Steven
Food banking generates large amount of structured and unstructured data typically stored and reported in spreadsheet format. The growing scale of data storage limit the effectiveness of traditional spreadsheet data exploration methods used by decision makers. Spreadsheets are generally convenient and easy to use for processing data, but less so for big data stores due to limitations such as capacity, computing performance, interactivity, and plotting capability. Visual analytics was proposed as an approach to improve information seeing using data provided by the Food Bank of Central and Eastern North Carolina. SAS Visual Analytics was used to generate interactive dashboards that included a geo map based on spreadsheet data for agency food distribution. Feedback from the Food Bank's management indicate substantial interest for visual analytics as a decision aid. A formal study is planned to evaluate decision-making performance with the dashboard in comparison to existing food bank methods.